Who is sitting next to you? Peer effects inside the classroom - Sok Chul Hong; Jungmin Lee (Quantitative Economics, 2017)
We examine college students' interaction within classrooms and estimate peer effects on their academic performance. We exploit a unique seating rule at a university in South Korea, known as the fixed-seat system. We propose a novel identification strategy based on students' repeated interaction. Our findings show that a student's performance in a class is significantly influenced by his or her next-seat neighbor's ability. The effect is heterogeneous, varying by student and class char- acteristics. Also quantile regressions reveal that peer effects are significant among below-average students and among those at the top end.
Keywords: C31; I21; 330; Peer effect; classroom seating rule; academic performance; college students; IV quantile regression; personality